Il capitalismo è ancora progressivo? - Perrotta, Cosimo (Studi e saggi, 2020)
This book explains the nature of capitalism both as a production system and as a historical process. Capitalism has superseded the systems based on rent and privileges, has freed up enterprise, brought in competition, set merit above corporative relations and patronage; has created a steady increase in wealth. The process has generated the development of the middle classes, a critical culture civil rights and democracy. However, the pursuit of profit has always tended to op-press the weaker categories and rob the less advanced economies. These two contrary trends cannot coexist indefinitely. Today the essential clash is between welfare for all and neoliberalism, based on increasing inequalities, rising financial rents and the exploitation of workers.